Evaluation of UV reflective mulches for protection against thrips (Thrips tabaci) in onion (Allium cepa) crops - van_Toor, R.F.; Till, C.; James, D.E.; Teulon, D.A.J. (New Zealand Plant Protection, 2004)
The efficacy of the ultraviolet (UV) reflective plastic mulch Extenday for preventing onion thrips (Thrips tabaci) from colonising onions was evaluated The mulch reflected 35 of incident UV at 250 nm wavelength and 25 of incident UV at 360 nm while bare soil reflected 11 and 4 UV at these wavelengths respectively In a field trial the total number of thrips at 8 weeks after transplanting was lower with mulch (185 thrips/ bulb) than in the control (280 thrips/bulb) However thrips populations were similar for both treatments in subsequent assessments When onions in seedling trays were placed adjacent to an onion field for 818 days during early mid and late summer aluminium foil which reflected UV 250 nm by 43 and UV 360 nm by 35 and Extenday did not reduce numbers of T tabaci compared to the control The use of reflective mulches for repelling thrips in onions does not appear promising